Battery Life Estimation for Embedded System - Prof. V.A.kulkarni; K alekar .Vikram V.; M ore Uday S.; K umbhar Onkar P (International Journal of Innovations in Engineering Research and Technology, 2021)
A battery system consist many battery cells with different characteristics to achieve reliable, efficient and extended utilization of battery. The battery management system provides individual level of battery. This level of b attery provide information about state of charge, state of health of the battery. The current battery technology provide module level with voltage sensor. The object of this project to determine and the display the supply frequency.